P212 Which patients may be eligible for pre-exposure prophylaxis (PrEP) for HIV?. (30th June 2016) - Bradshaw, Helen; Cunningham, Laura; Drayton, Rachel; Lomax, Nicola
Abstract : Background/introduction: HIV diagnoses remain high among men who have sex with men (MSM). Recent studies show promising results with reducing MSM HIV transmission. The PROUD and IPERGAY studies, using daily or 'on demand' Truvada as PrEP respectively, showed an 86% HIV transmission reduction. Clinical guidance and funding arrangements for PrEP are in development. We assessed PrEP eligibility amongst MSM attending our sexual health service. Aim(s)/objectives: To ascertain the proportion of MSM attending our service eligible for PrEP on clinical grounds and estimate the service and cost implications of introducing PrEP. Methods: 97 MSM attending from December 2014 to July 2015 were reviewed, including patients who had attended for post-exposure prophylaxis and STI screening. Patients were assessed against the PROUD study inclusion criteria to identify those who would benefit from PrEP. Results: No patients met any of the PROUD exclusion criteria. In a further 21% of notes, the exact number of episodes of UPAI, if any, was unclear although all other criteria were met. This suggests a range of 14–35% eligible for PrEP. We assumed all patients would continue having UPAI, were willing to comply with additional visits and were able to provide consent. The annual cost of Truvada is £356 per year. Further service cost analyses will be described. Discussion/conclusion: At least 14–35% of MSM attending our service may benefit from PrEP provision. Additional costs include STI screening, monitoring and care pathways will need to be introduced. However, the overall impact of PrEP may be to reduce new HIV diagnoses and the resultant care costs.